A coding method for 123 decision diagram pass transistor logic circuit synthesis - Avci, M; Yildirim, T (IEEE, 2003)
Pass transistor logic (PTL) circuits are known with their smaller silicon area usage, low power consumption and reduced delay advantages. 123 decision diagram is a very effective PTL synthesis tool based on binary decision. It realizes a logic function using NMOS pass, transistors with CMOS restoring buffers. At the same time layout of the circuit for two metal process is obtained by this diagram. A special coding is required to apply 123 decision diagram. Until now, the coding for the diagram has not been explained. In this paper a very easy and effective coding method for circuit synthesis and simplification with 123 decision diagram is proposed.
Keywords: DESIGN; Computer Science; Engineering